Genomics and Comparative Genomic Analyses Provide Insight into the Taxonomy and Pathogenic Potential of Novel Emmonsia Pathogens - Yang, Ying; Ye, Qiang; Li, Kang; Li, Zongwei; Bo, Xiaochen; Li, Zhen; Xu, Yingchun; Wang, Shengqi; Wang, Peng; Chen, Huipeng; Wang, Junzhi (Frontiers in Cellular and Infection Microbiology, 2017)
Over the last 50 years, newly described species of Emmonsia-like fungi have been implicated globally as sources of systemic human mycosis (emmonsiosis). Their ability to convert into yeast-like cells capable of replication and extra-pulmonary dissemination during the course of infection differentiates them from classical Emmonsia species. Immunocompromised patients are at highest risk of emmonsiosis and exhibit high mortality rates. In order to investigate the molecular basis for pathogenicity of the newly described Emmonsia species, genomic sequencing and comparative genomic analyses of Emmonsia sp. 5z489, which was isolated from a non-deliberately immunosuppressed diabetic patient in China and represents a novel seventh isolate of Emmonsia-like fungi, was performed. The genome size of 5z489 was 35.5 Mbp in length, which is approximately 5 Mbp larger than other Emmonsia strains. Further, 9,188 protein genes were predicted in the 5z489 genome and 16% of the assembly was identified as repetitive elements, which is the largest abundance in Emmonsia species. Phylogenetic analyses based on whole genome data classified 5z489 and CAC-2015a, another novel isolate, as members of the genus Emmonsia. Our analyses showed that divergences among Emmonsia occurred much earlier than other genera within the family Ajellomycetaceae, suggesting relatively distant evolutionary relationships among the genus. Through comparisons of Emmonsia species, we discovered significant pathogenicity characteristics within the genus as well as putative virulence factors that may play a role in the infection and pathogenicity of the novel Emmonsia strains. Moreover, our analyses revealed a novel distribution mode of DNA methylation patterns across the genome of 5z489, with > 50% of methylated bases located in intergenic regions. These methylation patterns differ considerably from other reported fungi, where most methylation occurs in repetitive loci. It is unclear if this difference is related to physiological adaptations of new Emmonsia, but this question warrants further investigation. Overall, our analyses provide a framework from which to further study the evolutionary dynamics of Emmonsia strains and identity the underlying molecular mechanisms that determine the infectious and pathogenic potency of these fungal pathogens, and also provide insight into potential targets for therapeutic intervention of emmonsiosis and further research.